‘Shitolokshya’: An Ecocritical study (‘শীতলক্ষ্যা’: একটি পরিবেশবাদী পাঠ) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
The geographical space where we live in which surrounds all the living and non-living entity is a very part of our environment. We, the living creatures relatably bound with a perpetual coherence and interdependence with environment. Our earth is beautiful because of its biological diversity. But nowadays this planet is facing various dangerous calamities. It hampers the constituents of the environment every movement, keeping natural balance has become a challenge. This sky-kissing ambitions and unnatural activities on the part of the living beings is responsiable for the degredation of the environment. As a result the glove is facing all the evil consequence caused by the human beings.               Human beings made their appearence in this world as the offspring of the nature. At the very inception of creation, the kind of environment, bestowed upon the hands of human beings by the nature, is gradually facing the fate of suffocating-death as a consequence of this race’s immeasurable thurst for pleasure. Specially, the first-world countries are consolidating their pillers of imperialistic-capitalism. As they are prone to overindulgence, the principle of ‘throw away culture’ has been added to their cherished legacy. In the second half of eighteenth century, Britain saw their industrial revolution and its expension throughout the world, inflicted the tendency of decadence of the nature. At first, the idea of ‘Environmentalism’ found its voice in the rich countries of first-world in the 70’s of last century. The primary objective of this idea is to establish a democratic resistance against the constant exploitation of natural environment and to protect the obvious process of bio-diversity and natural resources. The idea of ‘Environmentalism’, now defined as ‘Ecocriticism’ in literature, has now widely been discussed. In Bengali literature, its instances aren’t rare either. In my discussion I will illuminate how death of a pre-matuare women named shitolokshya and a river by the same name which describes the destruction of the locate khanepur metaphorically in the novel of ‘shitolokshya’ (2010) by Haripada Dutta. How the expension of modern high-tech civilization and industrialization affects the conventional native, village culture. How the culture of primitive cultivation and fishing dissolves itself day by day could easily be found at every layer. In this novel, the proverty striken villagers have been uprooted in the name of industrialization. So the farmers lost their ownland and fishermen lost their right on river that they enjoyed inherently.
Keywords: Environmentalism; Bengali Novel; Industrialization; Capitalism; Environmental Pollution; River Death; Livelihood